DEVELOPMENT PARADIGM OF THE INNOVATIVE TECHNOLOGY TRANSFER IN THE AGRO-INDUSTRIAL COMPLEX OF RUSSIA - Mikhail Yakovlevich VESELOVSKY; Vladimir Gavrilovich SAVENKO; Andrey Nikolaevich OSIPOV; Khatimat Nabievna GASANOVA; Dmitry Sergeyevich NATAROV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article emphasizes the significance and defines basic stages of agricultural advisory services formation in Russia, its actual status and current activities of its subjects, as well as development prospects. Based on the study of current development status of the contemporary services, main indicators of its activity and the demand for advisory services, the authors conclude that the country has established the basis of the agricultural advisory system, and formed the body of professional advisors, ready to provide quality advisory services that are largely becoming of demand. Special attention is paid to the innovative component of the agricultural advisory services functioning, consisting in informing about the scientific and technological achievements of Russian and foreign scientific organizations, advanced production practices, providing assistance in the modernization of production, increasing the level of knowledge of agricultural producers, as well as analyzing demand for advisory services. Based on the analysis of advisory group activities, forms and types of the most demanded services, the authors identify the main innovation and advisory directions in consulting activities. Moreover, it is noted that innovative direction should serve the basis of the industry modernization and be an object of state agrarian policy. Conceptualizing the activity priorities, the authors predict two directions of further development of the Russian system of agricultural advisory services. These are involvement of public institutions providing the state innovation policy, and more complete use of private commercial consulting structures providing assistance to rural entrepreneurs in the development of innovations and in other areas of their activities.